Effects of Calcium Treatment on Dragon Fruit [Hylocereus Polyrhizus (F.A.C. Weber) Britton & Rose] Quality and Activities of Polygalacturonase and Pectin Methylesterase - Chuni, Siti Hajar (2011)
Effects of different concentrations of calcium (Ca) from calcium chloride (CaCl2) on activities of two cell wall degrading enzymes; polygalacturonase (PG) and pectin methylesterase (PME) and fruit quality of dragon fruit (Hylocereus polyrhizus) were evaluated. Dragon fruit in this study were obtained from a commercial farm in Batang Benar in Nilai, Negeri Sembilan. Before any Ca treatments were given, it was important to establish the optimum temperature and pH for PG and PME enzymes as these were the two very important physical parameters influencing activity of an enzyme. PG and PME were assayed with different pH range of buffer solutions (pH 3.0 – 8.0) and different temperatures (30 – 70 °C) and results obtained were used in further experimentations. The activities of PG and PME were measured on dragon fruit of different maturity indices; index 3, 4 and 5. This study was carried out using a completely randomized design (CRD) with three replications. To determine the effect of Ca on PG and PME activities, different Ca concentrations (0, 2.5, 5 and 7.5 g/L Ca from CaCl2) were then treated to dragon fruit of two maturity indices (index 3 and 5) and stored for seven days at ± 20 °C. The experiment was conducted in a randomized completely block design (RCBD) with three replications. Effect of varying concentrations of Ca from CaCl2 (0, 2.5 and 7.5 g/L Ca from CaCl2) and dipping duration (0, 4, 8 and 12 mins) on PG and PME activities and fruit quality parameters (firmness, color, pH, calcium content, ascorbic acid content, titratable acidity and soluble solids concentration) of fresh-cut dragon fruit after five days of storage at 12 ± 1 oC were also examined. The experiment was carried out using RCBD with three replications. Results showed that the activity of PG was highest at 41 ºC (6.233 nkat/g) and at pH 6.0 (4.818 nkat/g) while PME activity reaches its maximum level at 47.8 ºC (60.864 neqv g-1 s-1) and at pH 5.8 (72.782 neqv g-1 s-1). Fruits of varying maturity indices have different activity of PG and PME activities. A very low PG activity was found in unripe H. polyrhizus (Index 3), but the activity of the enzymes increased as the fruit ripened (Indices 4 and 5) with their values being 1.26, 2.57 and 3.04 nkat/g respectively. In contrast, PME activity was higher in unripened fruit (Index 3) than fruit with maturity Index 4 and Index 5 being 25.73, 22.57 and 17.19 neqv g-1 s-1, respectively. It is proven that increasing calcium concentrations markedly reduced the activities of PG and PME enzymes in dragon fruit. At 7.5 g/L Ca from CaCl2, the activities of PG and PME were lowest followed by fruit treated with 5, 2.5 and 0 g/L Ca from CaCl2. The significant interaction between Ca concentration and duration of dipping showed the effect of Ca on the activity of PG and PME and dependent on duration of exposure to the chemical. Overall, dragon fruit treated with 7.5 g/L Ca from CaCl2 and eight minutes dipping significantly reduced the activities of PG and PME enzyme the lowest compared to other treatments. Duration of dipping did not affect fruit color, pH, titratable acidity and ascorbic acid content while soluble solids concentration and calcium content increased at a longer duration of dipping. There was an interaction found between Ca concentration and duration of dipping on firmness. The firmness of fruit slices treated at the highest Ca concentration (7.5 g/L) increased at the beginning of the treatment (2.31 N) but decreased as the duration increased to 8 and 12 mins being 1.91 and 2.18 N respectively. A correlation between parameters measured in this study showed that both PG and PME activities were negatively correlated with the fruit Ca content. The correlation result also showed that fruits with high Ca concentration contained low ascorbic acid content. Understanding on the cell wall degrading enzymes would give us a better opportunity to manipulate their activities, thus allowing us to extend the fruit economic life.